Tools and methods for assessing narrative competence in preschool children: A systematic review - Wu, Bo; Jamal Rizal, Razali; Tang, Yuying (Academy Publication, 2025)
This review intends to synthesize the assessment approaches in preschool children for narrative competence while focusing on some major characteristics like elicitation procedures, stimuli, types of tasks, and levels of analysis. With reference to 37 studies published between 2019 and 2024 in the WOS database, this review points to a diverse array of tools and methods of assessing narrative competence. Standardized and non-standardized tools have their own advantages and disadvantages, with the former providing cross-cultural consistency and the latter better capturing natural language samples; however, in the digital age, both also face common limitations. Different types of narrative tasks have different cognitive demands and apply to different assessment goals. In addition to conventional picture books, narrative stimulus materials include wordless books. However, there is a growing interest in digital stimulus materials, which offer interactivity and dynamic engagement and may fit better into modern educational environments. Future research can address these limitations by expanding the scope of included studies and considering the reliability and validity of assessment tools, while integrating digital technology and artificial intelligence to promote the dynamic, comprehensive, and real-time development of narrative competence assessment methods.